Dental students’ perception of a self-preference musical mobile app used as a relaxing tool in the clinical setting - Zarudin, Nur Irdina Nasmi; Ismail, Syamim Illya; Rajali, Aiemeeza; Nik Zulkifeli, Nik Rahayyu; Ahmad, Mas Suryalis; Mustafa, Nor Wati Nur Atikah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Diverse music activities may reduce stress and enhance well-being. However, using a musical mobile health application (app) as an intervention during dental treatment has not yet been established. Hence, a self-preference musical mobile app (ACOU@PLAY) has been created for use in clinical settings. Purpose: This study aims to assess the quality of the ACOU@PLAY app as a relaxing tool for dental students and compare the results with patients’ opinions. Methods: A total of 53% (n = 38) dental students and 47% (n = 35) patients were recruited to use the self-preference musical mobile app (ACOU@PLAY) for 10 minutes and watch a 5-minute pre-recorded video. Then, an evaluation was performed using a validated tool, the modified user version Mobile App Rating Skill (uMARS), which included a demographic survey. The uMARS questionnaire consists of five domains (engagement, functionality, aesthetics, information, and app subjective quality) using a 5-point Likert scale. Results: The average quality score of the app was 3.96 ± 0.509. The app received its highest rating for the information domains, with a mean score of 4.14 ± 0.577, and its lowest for subjective quality, with a mean score of 3.63 ± 0.565. Notable differences were observed in the ratings for engagement (p = 0.008) and aesthetics (p = 0.035) between dental students and patients, as well as significant differences in ratings based on gender in the domains of engagement (p = 0.007), functionality (p = 0.018), and aesthetics (p = 0.021). Conclusion: The self-preference musical mobile app (ACOU@PLAY) is well accepted by dental students and favored by patients with adequate qualities to be used in clinical settings.